Trend and forecast analysis of the changing disease burden of pancreatic cancer attributable to high fasting glucose in China, 1990–2021 - Song, Lichen; Chen, Ziyi; Li, Yongjie; Ran, Lirong; Liao, Dongwei; Zhang, Yuanyuan; Wang, Guangming (Frontiers in Oncology, 2024)
BackgroundPancreatic cancer (PC) is a malignant tumour with poor prognosis and high mortality, and high fasting plasma glucose (HFPG) is considered to be one of its important risk factors.MethodsPC disease burden data were obtained from the Global Burden of Disease Study 2021 (GBD 2021) database. Annual percent change (APC), average APC (AAPC), and 95% confidence interval (95% CI) were analysed using joinpoint linkpoint regression models to assess the trend of PC burden of disease between 1990 and 2021. An age-period-cohort model was used to estimate the independent effects of age, period, and cohort on PC burden, and data on PC mortality attributable to HFPG in China from 2022 to 2032 were analysed on the basis of a Bayesian age-period-cohort model projection.ResultsThe number of Pc deaths due to HFPG continue to rise in China from 1990 to 2021, with age-standardised mortality (ASMR) and age-standardised disability-adjusted life-year rates with increasing AAPC values of 1.12% (95% CI, 0.73–1.52) and 1.00% (95% CI, 0.63–1.37), respectively. Throughout the study, we found that the overall level of PC disease burden was significantly higher in men than that in women. In age-period-cohort analyses, the age effect of PC showed an increasing and then decreasing trend, the period effect showed an overall increasing trend during the study period, and the cohort effect showed an overall slow decreasing trend. In addition, the BAPC model predicted that ASMR is expected to decline significantly in both men and women from 2022 to 2032.ConclusionsIt was found that PC attributable to HFPG was generally on the rise in China from 1990 to 2021 and has been on the decline in recent years, and projections suggest that the country’s future PC disease burden will continue to show a downward trend. Age and period of birth are the main factors affecting the disease burden, especially in men and older age groups. Early prevention, regular screening, and research into the pathogenesis of PC have, therefore, become particularly important.